Transcriptase activity associated with rabies virion. - Kawai, A (1977)
Rabies virion-associated transcriptase activity was investigated in vitro and compared with that of the New Jersey serotype of vesicular stomatitis virus. The concentration of detergent that affected [3H]GMP incoporation into acid-insoluble material was significantly different for both viruses. Vesicular stomatitis virus New Jersey required 0.05 to 0.1% nonionic detergent, whereas rabies virion could not be fully activated unless 4 to 5% detergent was used. Other optimal conditions were as follows: 40 mM NaCl, 5 mM Mg2+, 40 mM Tris-hydrochloride (pH 7.4), 5 mM dithiothreitol, and 30 degrees C. The reaction required four nucleoside triphosphates. The initial rate of RNA synthesis by rabies virion enzyme was 140 pmol of GMP incorporated/mg of viral protein per h and linearly increased until about 8 h, with a slight initial lag phase. The enzyme activity that correlated with the content of L protein was highest when rabies virions were grown at 33 degrees C. The product was single-stranded RNA, which was complementary in base sequences to rabies viral RNA. Most of the RNA synthesized sedimented at 6-16S.